2022
DOI: 10.1186/s12984-021-00961-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of EMG-driven robot-assisted therapy versus task-oriented training on motor and daily function in patients with stroke: a randomized cross-over trial

Abstract: Background Robot-assisted hand training has shown positive effects on promoting neuromuscular control. Since both robot-assisted therapy and task-oriented training are often used in post-stroke rehabilitation, we raised the question of whether two interventions engender differential effects in different domains. Methods The study was conducted using a randomized, two-period crossover design. Twenty-four chronic stroke survivors received a 12-sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…One study was extracted two experimental groups ( Page et al, 2020 ). For randomized cross-over trial ( Chen et al, 2022 ), data before crossover were extracted. The study with fewest number of participants was carried out by Hayward ( n = 8, EG:4, CG:4) ( Hayward et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study was extracted two experimental groups ( Page et al, 2020 ). For randomized cross-over trial ( Chen et al, 2022 ), data before crossover were extracted. The study with fewest number of participants was carried out by Hayward ( n = 8, EG:4, CG:4) ( Hayward et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have found that the EMG-based robot improved the Fugl-Meyer assessment (FMA) score and spasticity of the upper extremity in post-stroke patients when compared with conventional therapy, ( Stein et al, 2007 ; Song et al, 2008 ; Hu et al, 2015 ; Nam et al, 2017 ). However, Chen et al, ( Chen et al, 2022 ), and Page et al, ( Stein et al, 2007 ; Page et al, 2013 ; Page et al, 2020 ), respectively found the efficacy of the EMG-based robot was not superior to task-oriented training and conventional hands-on manual therapy. Therefore, it remains unclear whether the effect of the EMG-based robot is superior to conventional therapies on upper limb function of stroke survivors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it can also provide corresponding training for patients with limb dysfunction to help restore the working ability of their limbs [62]. At present, robotic exoskeletons can be divided into the following four types, according to where they are worn: upper limb robotic exoskeletons [20][21][22][23][24], lower limb robotic exoskeletons [25][26][27][28][29][30], whole body robotic exoskeletons [15], and ground robotic exoskeletons [31,32].…”
Section: Robotic Exoskeletons Provide Site-specific Muscle Trainingmentioning
confidence: 99%
“…The increasing number of clinical trials has shown that robot-assisted therapy is effective in rehabilitation [15][16][17][18][19]. The conventional bilateral lower limb exoskeleton (BLLE) comprises powered dual robotic legs, facilitating rehabilitation training by driving both unaffected and affected lower limbs to perform a pre-programmed interactive gait control [20].…”
Section: Introductionmentioning
confidence: 99%